Professionals' Insights on Supervision in Portuguese Residential Care. - Magalhães, Eunice; Cerdeira, Joana (Child & Family Social Work, 2025)
The scarcity of evidence on how supervision in the child protection system (CPS) is developed, specifically in residential care, calls for further research on this issue. The aim of this study is to provide new insights on staff perceptions in residential care about supervision's strengths, opportunities, threats and weaknesses, as well as their conceptions about the impact of supervision in this context. A total of 94 professionals (Mage = 28.20, SD = 12.21) participated in this qualitative study. Participants completed an online survey consisting of six open‐ended questions and a sociodemographic questionnaire. Qualitative content analysis was performed using MAXQDA software and descriptive statistics using IBM SPSS. Participants perceived that supervision provided knowledge and interpersonal skills, allowing staff to receive support and guidance. Obtaining an external perspective was highlighted as a significant value of supervision, and the main constraints were related to economic and labour demands. Participants considered that supervision positively impacts mainly staff performance and the quality of intervention, with only residual references to the impacts on children or on the organizational structure. These findings can inform policies and practices aimed at improving supervisory mechanisms and structures. Changes in the recruitment and selection of supervisors, as well as guidelines outlining the roles and functions of supervision in care settings, are required.